Reassessing the Cross-National Relationship Between Income Inequality and Homicide Rates: Implications of Data Quality Control in the Measurement of Income Distribution - Messner, Steven F. (Journal of quantitative criminology, 2002)
A significant positive relationship between income inequality and homicide rates has been found in a large number of cross-sectional studies and a few longitudinal analyses; a theoretically interesting interaction effect between income inequality and social welfare has also been found. For the most part researchers have been willing to use generous quality criteria in collecting income-distribution data, to maximize sample size and thereby enhance statistical power and representativeness. In the present paper we use a recently developed data set with explicit quality ratings for the income-distribution data, which permits systematic assessment of the consequences of relying on income-distribution measures of varying quality in examining the inequality-homicide relationship. Our analyses reveal that the income inequality-homicide relationship is remarkably robust in cross-sectional analyses. Regardless of the quality of income-distribution data, we observe significant positive effects of the Gini coefficient on homicide rates in cross-sectional multivariate models. Consistent results are also observed when an interaction term for income inequality and decommodification is examined. The results of longitudinal analyses differ; we observe a significant positive effect of changes in inequality on changes in homicide rates only when income-distribution measures of low quality are used.